KAJIAN LITERARUR PENGARUH KUALITAS MAKANAN SUASANA DAN HARGA TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PADA RESTORAN ALL YOU CAN EAT - Reagan Brian (Program Studi Hospitality dan Pariwisata, 2020)
All you can eat restaurant is a restaurant with the concept of self service and buffet, does not provide services for its customers. So the other factors that affect customer satisfaction. The purpose of the study is to provide literature review about the effect of quality of food, atmospherics, and prices provided by restaurant all you can eat toward customer satisfaction and loyalty. This literature review try to suggest a theoretical framework from previous literature and previous studies. Since, at the present time the restaurant business competition is getting tougher. One key to the success of a restaurant is able to provide good quality services to satisfy the customers.